A randomised, double-blinded, placebo-controlled clinical study on intra-articular hyaluronan treatment in equine lameness originating from the metacarpophalangeal joint. Issue 1 (December 2016) - Niemelä, Tytti; Tulamo, Riitta-Mari; Hielm-Björkman, Anna
Abstract Background Intra-articular inflammation resulting in lameness is a common health problem in horses. Exogenous intra-articular hyaluronic acid has been shown to provide an analgesic effect and reduce pain in equine and human osteoarthritis. High molecular weight non-animal stabilized hyaluronic acid (NASHA) has gained popularity in the treatment of human arthritic conditions due to its long-acting pain-relieving effects. The aim of this study was to compare the response to treatment of lameness localized in the equine metacarpophalangeal joint injected with non-animal stabilized hyaluronic acid (NASHA) and placebo (saline). Twenty-seven clinically lame horses with a positive response to diagnostic intra-articular anaesthesia of the metacarpophalangeal joint and with no, or at most mild, radiographic changes in this joint were included in the study. Horses in the treatment group (n = 14) received 3 mL of a NASHA product intra-articularly, and those in the placebo group (n = 13) received an equivalent volume of sterile 0.9 % saline solution. Results The change in the lameness score did not significantly differ between NASHA and placebo groups (P = 0.94). Scores in the flexion test improved more in the NASHA group compared with placebo (P = 0.01). The changes in effusion and pain in flexion were similar (P = 0.94 andP = 0.27, respectively) when NASHA and placebo groups were compared. A telephone interview follow-up of the owners three months post-treatment revealed that 14 of the 21 horses (67 %) were able to perform at their previous level of exercise. Conclusions In the present study, a single IA NASHA injection was not better than a single saline injection for reducing lameness in horses with synovitis or mild osteoarthritis. However, the results of this study indicate that IA NASHA may have some beneficial effects in modifying mild clinical signs but more research is needed to evaluate whether the positive effect documented ie. reduced response in the flexion test is a true treatment effect.